Participatory Approach to Relocate Villages from Protected Area : a Lesson from Chandaka - Dampara Wildlife Sanctuary - Singh, K. R. (Indian Forester, 1997)
Rehabilitation of villagers from protected area is one of major problems of forest and wildlife managers in India. The present case study involving relocation of a part of village from Chandaka - Dampara Wildlife Sanctuary near Bhubaneswar, based on participatory approach, is one of the success stories which throws light on the possible methodology for relocating villagers from protected area by developing a sense of mutual trust and understanding. The method can be applied also for any Community problem, rehabilitation proposal arising due to irrigation, mining, industrial or other project and even for Community Development.